Orofacial manifestations and dental management of systemic lupus erythematosus: A review. (3rd March 2020) - Benli, Merve; Batool, Fareeha; Stutz, Céline; Petit, Catherine; Jung, Sophie; Huck, Olivier
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune multisystem disease with numerous clinical manifestations. There is no consensus about the ideal oral management for this group of patients to date. This review aimed to describe the broad spectrum of orofacial and clinical manifestations and their therapeutic approaches. Studies concerning orofacial manifestations of SLE and dental treatment modalities were selected by a literature search (1978–2019) using Google Scholar, PubMed/MEDLINE electronic databases. The initial search strategy provided a total of 129 articles, and of these, 30 were included for qualitative synthesis. The reviewed studies revealed that SLE patients are more at risk of compromised oral and dental health exhibiting increased risk of periodontal diseases and temporomandibular joint disorders. The use of systemic drugs especially immunosuppressive and anticoagulants in SLE patients may also influence their oral management. Results emphasize the need to carry out, at an early stage of the disease, an appropriate oral management of these patients to improve oral health‐related quality of life and to prevent the need of more invasive therapeutics. A multidisciplinary approach is needed for dental and medical management of such patients.